1999
DOI: 10.1136/thx.54.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Long term effects of inhaled corticosteroids in chronic obstructive pulmonary disease: a meta-analysis

Abstract: Conclusions-This meta-analysis in patients with clearly defined moderately severe COPD showed a beneficial course of FEV 1 during two years of treatment with relatively high daily dosages of inhaled corticosteroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1
4

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(55 citation statements)
references
References 14 publications
2
48
1
4
Order By: Relevance
“…On the other hand, a meta-analysis of three studies published between 1983 and 1996 showed a significant beneficial effect of inhaled corticosteroids over placebo on the course of the prebronchodilator FEV 1 during 2 years of treatment. 34 From our analysis of the MEFV curves, we hypothesise that the anatomical location of the anti-inflammatory effect of inhaled steroids is in the smaller airways. Significant changes were observed in MEF 50 and MEF 25 .…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, a meta-analysis of three studies published between 1983 and 1996 showed a significant beneficial effect of inhaled corticosteroids over placebo on the course of the prebronchodilator FEV 1 during 2 years of treatment. 34 From our analysis of the MEFV curves, we hypothesise that the anatomical location of the anti-inflammatory effect of inhaled steroids is in the smaller airways. Significant changes were observed in MEF 50 and MEF 25 .…”
Section: Discussionmentioning
confidence: 96%
“…Grunsven et al 9 reported no signifi cant differences in exacerbation rates between the group on inhaled corticosteroids and the group on placebo. Results of a meta-analysis by Sin et al 12 are consistent with our fi ndings.Point estimates from our analyses, however, are more precise because of the greater number of component studies.…”
Section: Inhaled Corticosteroids and Copdmentioning
confidence: 96%
“…Most published studies and systematic reviews [8][9][10] 11 Only one meta-analysis focused primarily on health outcomes 12 ; none of these systematic reviews took observational evidence for adverse events into consideration. Limiting adverse events assessment to randomized controlled trials (RCTs) risks missing rare but potentially severe adverse events, such as osteoporotic fractures, glaucoma, or cataract, which RCTs cannot reliably assess because of limitations of sample sizes and study durations.…”
Section: 4 Inhaled Corticosteroids and Copdmentioning
confidence: 99%
“…Also a recent metaanalysis points to a positive effect on the lung function in COPD [9]. But most studies show that this positive effect is no more than an initial effect during the first months of use.…”
mentioning
confidence: 99%